Multiple nodules on the left cheek represented pseudolymphomatous folliculitis. Issue 6 (4th May 2016) - Horikiri, Masaru; Abe, Naho; Ueda, Kazuki
Key Clinical Message: Pseudolymphomatous folliculitis (PLF) is a rare lesion. Sometimes, the clinical appearance is characterized by multiple large, firm violaceous nodules. In cases with multiple lesions, such biopsy should be performed on one lesion, and once PLF is determined, monitoring for the remained tumor is considered to be the best treatment. Abstract : Pseudolymphomatous folliculitis (PLF) is a rare lesion. Sometimes, the clinical appearance is characterized by multiple large, firm violaceous nodules. In cases with multiple lesions, such biopsy should be performed on one lesion, and once PLF is determined, monitoring for the remained tumor is considered to be the best treatment.